The Revolving Door of Adenovirus Cell Entry: Not All Pathways Are Equal - Davor Nestić; Ksenija Božinović; Isabela Pehar; Rebecca Wallace; Alan L. Parker; Dragomira Majhen (MDPI AG, 2021)
Adenoviruses represent exceptional candidates for wide-ranging therapeutic applications, from vectors for gene therapy to oncolytics for cancer treatments. The first ever commercial gene therapy medicine was based on a recombinant adenovirus vector, while most recently, adenoviral vectors have proven critical as vaccine platforms in effectively controlling the global coronavirus pandemic. Here, we discuss factors involved in adenovirus cell binding, entry, and trafficking; how they influence efficiency of adenovirus-based vectors; and how they can be manipulated to enhance efficacy of genetically modified adenoviral variants. We focus particularly on endocytosis and how different adenovirus serotypes employ different endocytic pathways to gain cell entry, and thus, have different intracellular trafficking pathways that subsequently trigger different host antiviral responses. In the context of gene therapy, the final goal of the adenovirus vector is to efficiently deliver therapeutic transgenes into the target cell nucleus, thus allowing its functional expression. Aberrant or inefficient endocytosis can impede this goal, therefore, it should be considered when designing and constructing adenovirus-based vectors.